Fatigue crack growth based on the dislocation-free zone (DFZ) model. (November 2015) - Ge, Jingran; Sun, Yi; Wang, Ting; Liu, Shiwei; Bai, Yarui
Highlights: A microscopic mechanism model for fatigue crack growth is presented. The value of J -integral under cyclic loading is determined applying cohesive model. Effect of cyclic plasticity on fatigue crack growth is considered. The proposed model is proved to have a general good accuracy. Abstract: In the present work, a microscopic mechanism model is presented to predict fatigue crack growth, which is developed based on the combination of fracture physics and cyclic plasticity effect. The gradual degradation of materials near crack tip is regarded as a result of cyclic plastic deformation. The J -integral within cohesive zone under cyclic loading is selected as the crack growth criterion, and determined based on dislocation-free zone and cohesive theory. The dislocation-free zone model is validated with experimental data from literature. It has been shown that the results predicted by the proposed model agree well with the experiment.